Counterweight - Tyuna (Pantheon Books, 2022)
"For fans of the worlds of Philip K. Dick, Squid Game, and Severance: An absorbing tale of corporate intrigue, political unrest, unsolved mysteries, and the havoc wreaked by one company's monomaniacal endeavor to build the world's first space elevator-from one of South Korea's most revered science fiction writers, whose identity remains unknown. On the fictional island of Patusan-and much to the ire of the Patusan natives-the Korean conglomerate LK is constructing an elevator into Earth's orbit, gradually turning this one-time tropical resort town into a teeming travel hub: a gateway to and from our planet. Up in space, holding the elevator's "spider cable" taut, is a mass of space junk known as the counterweight. And it's here that lies the key-a trove of personal data left by LK's former CEO, of dire consequence to the company's, and humanity's, future. Racing up the elevator to retrieve the data is a host of rival forces: Mac, the novel's narrator and LK's Chief of External Affairs, increasingly disillusioned with his employer; the everyman Choi Gangwu, unwittingly at the center of Mac's investigations; the former CEO's brilliant niece and his power-hungry son; and a violent officer from LK's Security Division, Rex Tamaki-all caught in a labyrinth of fake identities, neuro-implant "Worms," and old political grievances held by the Patusan Liberation Front, the army of island natives determined to protect their sovereignty. Conceived by Djuna as a low-budget science fiction film, with literary references as wide-ranging as Joseph Conrad and the Marquis de Sade, The Counterweight is part cyberpunk, part hardboiled detective fiction, and part parable of Korea's neocolonial ambition and its rippling effects"--